BONE DIAGENESIS: METHODS OF STUDY AND ANALYSIS, AND ITS CONTRIBUTION TO PALEONTOLOGY - Σταθοπούλου, Ε. (Bulletin of the Geological Society of Greece, 2006)
The objective of this paper is to present bone diagenesis, the diagenetic alterations that occur in bones, the parameters that affect it as well as its importance to Palaeontology, as a modern tool with numerous applications. The most important analytical techniques and methods used today to study bone diagenesis are also presented.